Scalar Form Factor of the Pion in the Kroll-Lee-Zumino Field Theory - C. A. Dominguez; M. Loewe; M. Lushozi (Advances in High Energy Physics)
The renormalizable Kroll-Lee-Zumino field theory of pions and a neutral rho-meson is used to determine the scalar form factor of the pion in the space-like region at next-to-leading order. Perturbative calculations in this framework are parameter-free, as the masses and the rho-pion-pion coupling are known from experiment. Results compare favorably with lattice QCD calculations.